1984
DOI: 10.1182/blood.v64.5.981.981
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand's disease in the myeloproliferative syndrome

Abstract: An acquired hemorrhagic disorder developed in two patients in association with postsplenectomy thrombocytosis and leukocytosis during the course of the myeloproliferative syndrome. The presence of acquired von Willebrand's disease in these individuals was demonstrated by a decrease or absence of the larger von Willebrand factor (vWF) multimers, alteration of the repeating vWF multimeric “triplet,” decreased ristocetin cofactor activity (vWF:RCo), and prolonged bleeding time. The bleeding stopped in both patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(106 citation statements)
references
References 17 publications
2
102
0
2
Order By: Relevance
“…This phenomenon is not restricted to MPD and has also been described in patients with reactive thrombocytosis, suggesting a primary effect of absolute platelet number as opposed to dysfunctional clonal platelets (Budde et al, 1993). This would be consistent with the observed resolution of the specific laboratory abnormality with platelet cytoreduction (Budde et al, 1984;Budde et al, 1993;van Genderen et al, 1997b;Michiels et al, 2001).…”
Section: Pathogenesissupporting
confidence: 84%
“…This phenomenon is not restricted to MPD and has also been described in patients with reactive thrombocytosis, suggesting a primary effect of absolute platelet number as opposed to dysfunctional clonal platelets (Budde et al, 1993). This would be consistent with the observed resolution of the specific laboratory abnormality with platelet cytoreduction (Budde et al, 1984;Budde et al, 1993;van Genderen et al, 1997b;Michiels et al, 2001).…”
Section: Pathogenesissupporting
confidence: 84%
“…However, the presence of MG has not always been evident in several of the haematological and nonhaematological disorders described in association with AVWD. These conditions have included chronic lymphoproliferative (Goudemand et al, 1988) or myeloproliferative disorders (Budde et al, 1984).…”
mentioning
confidence: 99%
“…10 Various abnormalities of circulating von Willebrand factor (VWF) have been described in patients with MPNs, usually associated with severe thrombocytosis. [11][12][13] The main abnormalities consisted of loss of larger VWF multimers and high proteolysis of VWF, all associated with thrombocytosis, mostly resulting in bleeding. 11,14,15 In a previous study on ET, we observed a deficiency of VWF activity and selectively of large VWF multimers over a wide range of platelet counts, rather than in patients with severe thrombocytosis only.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The main abnormalities consisted of loss of larger VWF multimers and high proteolysis of VWF, all associated with thrombocytosis, mostly resulting in bleeding. 11,14,15 In a previous study on ET, we observed a deficiency of VWF activity and selectively of large VWF multimers over a wide range of platelet counts, rather than in patients with severe thrombocytosis only. 16 This acquired VWF deficiency was likely a continuous phenomenon, driven by high ongoing in vivo platelet activation, which is the hallmark of ET, with consequent platelet-dependent VWF consumption.…”
Section: Introductionmentioning
confidence: 99%